2017
DOI: 10.1097/mat.0000000000000460
|View full text |Cite
|
Sign up to set email alerts
|

Scaling the Low-Shear Pulsatile TORVAD for Pediatric Heart Failure

Abstract: This article provides an overview of the design challenges associated with scaling the low-shear pulsatile TORVAD ventricular assist device (VAD) for treating pediatric heart failure. A cardiovascular system model was used to determine that a 15 ml stroke volume device with a maximum flow rate of 4 L/min can provide full support to pediatric patients with body surface areas between 0.6 to 1.5 m2. Low shear stress in the blood is preserved as the device is scaled down and remains at least two orders of magnitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 32 publications
(33 reference statements)
0
17
0
1
Order By: Relevance
“…The pulsatile TORVAD pump is a 15 mL stroke volume device with a maximum flow rate of 4 L/min. This pump can provide full support to pediatric patients with BSAs between 0.6 and 1.5 m 2 .…”
mentioning
confidence: 99%
“…The pulsatile TORVAD pump is a 15 mL stroke volume device with a maximum flow rate of 4 L/min. This pump can provide full support to pediatric patients with BSAs between 0.6 and 1.5 m 2 .…”
mentioning
confidence: 99%
“…[25][26][27] Of note, the new design of next-generation LVADs such as toroidal-flow LVAD has focused on providing full hemodynamic support with lower shear rate of approximately 2857 s −1 to reduce blood trauma. 46,47 Second, our current blood-shearing experiments were performed at room temperature instead of body temperature (37°C) and aggregate size was assessed from two-dimensional images rather than as three-dimensional volumes. Third, the current work was focused on understanding the mechanobiology of vWF multimers interaction with platelets under shear and how that influences the formation sizes of platelet aggregates.…”
Section: Limitationsmentioning
confidence: 99%
“…2,3,6 A pVAD is a volume displacement pump in which the blood is not propelled by shear or centrifugal forces, but which instead works with a pumping mechanism that is more like the native heart. Other pulsatile pumping concepts proposed such as the TORVAD 14 exist, but exceed the WSS levels suitable for endothelialization. Computational fluid dynamics (CFD) studies with displacement pump models mimicking existing pVAD shapes have shown maximum WSS to be between 10 and 16 Pa. 15,16 Physiological levels of WSS were reported to average around 6 Pa 17,18 and peak stresses in human pre-capillary arterioles close to 15 Pa. 19 Additionally, the ECs are exposed to a combined load of shear and strain on the pulsating membrane in a pVAD.…”
Section: Rebholz Et Almentioning
confidence: 99%
“…A pVAD is a volume displacement pump in which the blood is not propelled by shear or centrifugal forces, but which instead works with a pumping mechanism that is more like the native heart. Other pulsatile pumping concepts proposed such as the TORVAD exist, but exceed the WSS levels suitable for endothelialization. Computational fluid dynamics (CFD) studies with displacement pump models mimicking existing pVAD shapes have shown maximum WSS to be between 10 and 16 Pa .…”
Section: Introductionmentioning
confidence: 99%